The Use of Web 2.0 Tools and Technologies in English Language Teaching-Learning Process - Roy , Piu (Gyan Management Journal, 2023)
English language instruction increasingly makes use of web 2.0 tools and technologies as the most cutting-edge example of internet-based technology. Wikis, blogs, podcasts, social networks, and video conferencing are some of the most common examples of Web 2.0 technologies that have shown their use in language instruction and study. In the last ten years, Web 2.0 has become an essential part of the educational process, both within and outside the traditional classroom setting. Almost all language classes have used various technological tools and resources in recent years. Using multiple technologies has facilitated and improved students’ ability to learn new languages. The use of technology enables teachers to adapt classroom activities, which ultimately speeds up the language acquisition process. It is becoming more critical for teachers to use the tools and technology offered by Web 2.0 to encourage language learning in their classes. This research investigates the impact that contemporary technology has on the process of learning English as a second or foreign language. We looked at various mindsets to see what technology motivates English language learners to enhance their learning abilities. The researcher defines technology and explains how technology may be integrated into educational settings, namely language courses. It reviews previous studies on using Web 2.0 tools and technologies to enhance language learning abilities and makes recommendations for the improved use of these technologies, which aid students in improving their learning abilities. In addition, it reviews previous studies on using Web 2.0 tools and technologies to enhance language learning abilities. The anticipated results from the previously published research demonstrate that students’ language-learning abilities improve when they effectively use emerging technologies.